OC-105 Experience in polypectomy training and assessment: an international survey. (22nd June 2015) - Patel, K; Rajendran, A; Faiz, O; Rutter, M; Rutter, C; Jover, R; Koutroubakis, I; Januszewicz, W; Ferlitsch, M; Dekker, E; MacIntosh, D; Ng, SC; et al.
Abstract : Introduction: Colonoscopy is widely practised to reduce rates of colorectal cancer, although it does not confer absolute protection. The most hazardous part of colonoscopy is polypectomy, accounting for the majority of serious complications. It is unclear whether countries around the world have highlighted polypectomy as a specific skill that needs to be taught. The objective of the study was to assess both trainees' and trainers' experience of polypectomy training in countries around the world. Method: Colonoscopy trainers from 19 countries worldwide (Figure 1) were asked to provide access to local trainers and trainees who would be invited to participate in a survey. An online survey was created asking about trainees' experience of instruction and trainers' experience of teaching polypectomy skills. Results: Data were obtained from 610 colonoscopists- 348 (57.0%) trainers and 262 (43.0%) trainees. Most (79.6%) of the trainers surveyed were involved in polypectomy assessment weekly. 51.4% of those surveyed said that they used a specific framework when assessing polypectomy. 90.5% of trainees had a primary specialty of medical gastroenterology. The trainees had a breadth of colonoscopic experience, 31.7% having completed more than 500 colonoscopies and 38.2% fewer than 200 procedures. 51.1% stated that the principles of polypectomy had only been taught intermittently. Most (64.1%, 168 respondents) trainees had never been taught the principles of EMR. Only 53.1% of trainees had ever had their polypectomy technique formally assessed by any trainer. Of the 177 trainees who stated that they were competent at polypectomy, 70 (39.5%) had never had a formal evaluation of their polypectomy technique. Conclusion: This study, the only in the literature, shows that polypectomy training is variable worldwide with low prevalence of formal competency assessment. There is a need to a) understand the learning curve for polypectomy, b) develop an international consensus defining optimal training methods and c) develop a framework of competency assessment. This should improve the safety of polypectomy and the effectiveness of colonoscopy in preventing colorectal cancer. Disclosure of interest: None Declared. Reference: The authors would like to acknowledge the contribution of all 610 respondents and in particular the local training faculty who facilitated this study